Advanced Engineering Mathematics - Kreyszig, Erwin (New Delhi, Wiley India Pvt. Ltd, 2022)
The tenth edition of this bestselling text includes examples in more detail and more applied exercises; both changes are aimed at making the material more relevant and accessible to readers. Kreyszig introduces engineers and computer scientists to advanced math topics as they relate to practical problems. It goes into the following topics at great depth differential equations, partial differential equations, Fourier analysis, vector analysis, complex analysis and linear algebra / differential equations.
It includes Appendix and Index.
Keywords: Mathematics; Engineering Mathematics